Methodology for determining the most effective scenario for deploying a transport corridor - Kaptur, V.; Kniazieva, O.; Каптур, В. А.; Князєва, О. А. (Харківський національний автомобільно-дорожній університет, 2022)
In the context of deepening integration processes, the leading role belongs to the formation of international transport corridors (ITC), the development of which is faced with the need to determine its potential efficiency. Most scientific developments do not consider the issues of determining the effectiveness of the codeployment of several infrastructures in the framework of the scenario analysis of ITC projects. The purpose of the work is to form scientific and methodological approaches to determining the most effective scenario for the design of a transport corridor in the context of the co-deployment of several infrastructure flows. Research methods. The information base includes international regulations, statistical information and UN directives. Several methodology of research of scientific cognition have been applied, theoretical generalization, empirical analysis, comparison, forecasting, etc. Findings. A generalized algorithm for determining the most appropriate model for the development of ITC has been developed. A method is proposed for determining promising infrastructure flows, based on an assessment of demand and considering the unevenness of the load, the influence of the internal and external contours. An approach has been developed to determine capital investments and maintenance (operational) costs based on the division of technological processes into non-trivial and scalable. It is proposed to use indicators of net present value (NPV) and an index of the rate of specific growth in value (IS) as criteria for efficiency. The proposed approach was tested on the example of ITC Almaty (Kazakhstan) – Cholpon-Ata (Kyrgyzstan), which showed that the project with the existing flows is ineffective and requires a different design solution or a significant increase in flows. Originality. The improvement of methods for evaluating design solutions in the design of ITC in terms of determining the potential flows of each of the possible scenarios (by direct calculation, extrapolation or reverse method) with the subsequent calculation of the potential efficiency of each. Practical value. Offered approach to determining the most effective scenario for the deployment of a transport corridor based on the application of a scenario approach with a subsequent assessment of each scenario.
Методика визначення найбільш ефективного сценарію розгортання транспортного коридору
Keywords: international transport corridor; flows; scenario; efficiency; міжнародний транспортний коридор; потоки; сценарій; ефективність; 330.131.52, 004.735, 625.111; 10.30977/PPB.2226-8820.2022.28.4